Future perspectives for PDE5 inhibitors bridging the gap between cardiovascular health and psychological status - Andrea Sansone; Eugenia Guida; Susanna Dolci; Valeria Frangione; Amanda Asso; Gilberto Bellia; Emmanuele A. Jannini (Basic and Clinical Andrology)
Abstract The serendipitous discovery that inhibiting type 5 phosphodiesterase (PDE5) using sildenafil, a potent PDE5 inhibitor (PDE5i) initially developed for cardioprotection, introduced the possibility of orally managing erectile dysfunction (ED) led to an increase in research data, which are currently considered groundbreaking for the new discipline of sexual medicine. Findings from a number of laboratories and clinics around the world unanimously demonstrated the following: (i) the major cause of ED is directly or indirectly related to cardiovascular disease (CVD); (ii) ED and CVDs share the same risk factors, which are related mainly to lifestyle choices; (iii) the first therapeutic approach to both ED and CVDs is to transform harmful lifestyles into virtuous lifestyles; and (iv) PDE5is in general, particularly sildenafil, are very safe, if not protective, for use in CVD patients. However, the use of PDE5is has faced several challenges. Many patients and some healthcare providers (HCPs) often share the misconception that using these drugs can increase the risk of CVD. Some patients might desire to fulfill the unmet need for privacy linked to the stigma of being treated for ED or might be enticed by the idea of buying drugs online, either because of shame or cheaper prices, without knowing the risks associated with counterfeit drugs. The aim of this narrative revision of the current literature is to demonstrate that (i) the orodispersible film of sildenafil is safe from a CV perspective; (ii) it is a discreet formulation that respects the need for privacy; and (iii) it is virtually the unique PDE5i formulation too expensive to produce outside the correct channels, making it impossible to be counterfeit.